1989
DOI: 10.1016/0169-4332(89)90976-8
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of boron and its reaction with oxygen on Rh

Abstract: The segregation of boron and its reactivity towards oxygen has been investigated by means of AES, XPS, UPS and ELS (in the electronic range) in the temperature range 11)0-1300 K. The segregation of boron in a Rh foil started from 700 K. The ~egregated boron produced a peak in XPS for the B(ls) level a~ 187.8 eV and emissions in UPS at 4,0 and 8,6-9.0 eV for B(2p) and B(2sp2), respectively, Analysis of the results suggested that the segregated boron on Rat foil mainly forms dimers or islands, instead of isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 22 publications
6
15
0
Order By: Relevance
“…6B). The formation of a B O bond is also justified by the fine structure of B(KVV) and O(KVV) AES signal obtained in the interaction of oxygen with boron containing Rh at 300 K [32]. The AES transition of adsorbed oxygen on a B/Rh surface appeared at 513 eV at low exposure.…”
Section: Adsorption and Decomposition Of No On Boron Containing Rhmentioning
confidence: 94%
See 2 more Smart Citations
“…6B). The formation of a B O bond is also justified by the fine structure of B(KVV) and O(KVV) AES signal obtained in the interaction of oxygen with boron containing Rh at 300 K [32]. The AES transition of adsorbed oxygen on a B/Rh surface appeared at 513 eV at low exposure.…”
Section: Adsorption and Decomposition Of No On Boron Containing Rhmentioning
confidence: 94%
“…The segregation of boron was pointed out in earlier works [17][18][19][20][21][22][23][24]32]. It has been observed that boron is a major bulk impurity (17 ppm) in Rh.…”
Section: General Features Of Segregated Boron On Rhodium Surfacesmentioning
confidence: 96%
See 1 more Smart Citation
“…The low BE peak is the larger of the two, and is assigned as above to elemental boron. The higher BE peak is believed to correspond to an oxide, but it is not clear whether it is the most common boron oxide, B203, or a defective suboxide or both; the BE of 191.2 eV has nearly the BE shift (4.1 eV, referenced to elemental boron) reported [5] in the literature for BzOs (4.6 eV).…”
Section: Patchy Boron Layer Modelmentioning
confidence: 96%
“…The position of this peak is close to that assigned below to boron nitride, but no nitrogen was detected in this particular sample. Some authors have discussed boron suboxides like BxOz at surfaces [5]; perhaps there is a range of oxygen-deficient possibilities between B and B203.…”
Section: Patchy Boron Layer Modelmentioning
confidence: 99%